Acculturation of international graduate students in U.S. higher education institutions - Gao, Bing; Wesely, Pamela M. (Journal of International Students, 2024)
Every year, the U.S. witnesses an increase in the number of international students pursuing higher education. Researchers, who have focused primarily on international undergraduates, have suggested that international students often encounter various acculturative stressors while adapting to new academic and living environments. Moreover, there is expanding research on coping strategies adopted by most international undergraduates to manage acculturative stressors. Although the number of international graduate students (IGSs) has surpassed that of international undergraduates in the U.S. since 2020, their experiences in higher education contexts have still received relatively less attention than their undergraduate counterparts. This study employed Yakushko’s (2010) theoretical model of stress and coping strategies to examine the acculturation experiences of ten IGSs from three U.S. higher education institutions. The findings revealed common acculturative stressors for IGSs, the factors in those stressors, and the coping strategies employed by IGSs and the corresponding consequences.